Pengembangan Instrumen Asesmen Berbasis Enam Aspek Pemahaman dalam Kerangka Understanding by Design (UbD) Pada Materi Termokimia Kelas XI SMA Sederajat - Agustia, Aufa; Haryati, Sri; Holiwarni, Betty (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop an assessment instrument based on the six facets of understanding within the Understanding by Design (UbD) framework, specifically for thermochemistry material. The research adopted the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study was conducted from February to May 2025 at the Faculty of Teacher Training and Education, University of Riau, with field testing carried out at SMA Negeri 4 Pekanbaru and SMA Negeri Plus Provinsi Riau. Data were collected through expert validation, one-on-one trials, small group trials, and item characteristic analysis. Expert validation results indicated that the developed instrument is valid in terms of content, construct, and language, with average percentage scores of 100%, 96.63%, and 100%, respectively. Student responses to the instrument fell into the “very good” category, with an average score percentage of 91.08%. Teacher responses also indicated a “very good” category, with an average score percentage of 95.83%. The item analysis revealed that the instrument has strong construct validity, high reliability, and appropriate levels of difficulty and discrimination. Therefore, this assessment instrument is deemed suitable for measuring students’ understanding in alignment with the learning objectives outlined in the Merdeka Curriculum.